2015
DOI: 10.1007/s10722-015-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of resistance to Bemisia tabaci Genn. in closely related wild relatives of cultivated tomato based on trichome type analysis and choice and no-choice assays

Abstract: The sweetpotato whitefly, Bemisia tabaci Genn., is a major pest of tomato (Solanum lycopersicum) and other crops throughout the tropics and subtropics. The objectives of this study were to characterize 255 accessions of S. galapagense, S. cheesmaniae and S. pimpinellifolium for trichome types, and to evaluate selected accessions with high densities of glandular trichomes for resistance to whitefly. Twenty-two accessions classified as either sparse or abundant for type IV trichomes were selected and evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 51 publications
7
66
1
Order By: Relevance
“…Ben-Israel et al (2009) found that spherical-shaped type VI trichomes accumulated higher concentrations of methylketone compared to lobe-shaped type VI trichomes in F 2 interspecific populations derived from S. habrochaites f. glabratum C. H. Müll. Similar associations were found between the presence of spherical-shaped type VI trichomes and whitefly resistance of VI030462 based on numbers of whitefly adults, nymphs, pupa, and eggs in the choice bioassay, and adult mortality and number of eggs from the no-choice bioassays (Rakha et al 2015), suggesting the presence of similar mechanisms of resistance to spider mite and whitefly in this accession. Besides high type IV trichome density, whitefly resistance has been associated with sparsity or absence of type V trichomes (Butter and Vir 1989;Firdaus et al 2012;Lucatti et al 2013;Rakha et al 2015).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Ben-Israel et al (2009) found that spherical-shaped type VI trichomes accumulated higher concentrations of methylketone compared to lobe-shaped type VI trichomes in F 2 interspecific populations derived from S. habrochaites f. glabratum C. H. Müll. Similar associations were found between the presence of spherical-shaped type VI trichomes and whitefly resistance of VI030462 based on numbers of whitefly adults, nymphs, pupa, and eggs in the choice bioassay, and adult mortality and number of eggs from the no-choice bioassays (Rakha et al 2015), suggesting the presence of similar mechanisms of resistance to spider mite and whitefly in this accession. Besides high type IV trichome density, whitefly resistance has been associated with sparsity or absence of type V trichomes (Butter and Vir 1989;Firdaus et al 2012;Lucatti et al 2013;Rakha et al 2015).…”
Section: Discussionsupporting
confidence: 72%
“…Mean ± SE (n = 10) followed by different letters are significantly different according to according to least significant difference (LSD) test at p \ 0.05 habrochaites f. glabratum (PI 134417, PI 251304, PI 134418 and PI 126449), S. habrochaites (PI 127826, LA1777, LA 1740 and LA 2860) and S. pennellii (LA 716, LA 2963 and LA 2580) (Gentile et al 1969;Snyder and Carter 1984;Antonious and Snyder 2006;Saeidi and Mallik 2006;Onyambus et al 2011;Bleeker et al 2012;Lucini et al 2015). More than 250 wild tomato accessions were recently screened at AVRDC including S. galapagense, S. cheesmaniae and S. pimpinellifolium and high levels of whitefly (B. tabaci) resistance were identified in one or more accessions of each species (Rakha et al 2015). These species are closely related to cultivated tomato and introgression of resistance into cultivated tomato from these species should be easier and faster compared to the green-fruited species S. pennellii, and S. habrochaites (Rick, 1971;Peralta et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations